Geophysical constraints on the flexural subsidence of the Denver Basin - Abdullin, Ayrat, author; Harry, Dennis L., advisor; Egenhoff, Sven, committee member; Lefsky, Michael, committee member (Colorado State University. Libraries, 2012)
The Denver Basin is an asymmetric Laramide (Late Cretaceous through Eocene) foreland basin covering portions of eastern Colorado, northwestern Kansas, southwestern Nebraska, and southeastern Wyoming, USA. It is bordered on the west by the Rocky Mountain Front Range Uplift, a basement cored Laramide anticline bounded by thrust faults, and on the east by the Great Plains and stable North American craton. A ~400 mGal negative Bouguer gravity anomaly exists over the Denver Basin and Front Range Uplift, with its minimum located over the highest topography in the central part of the uplift, approximately 100 km west of the Denver Basin. This study examines three hypotheses concerning the isostatic state of the basin and adjacent Front Range Uplift. These hypotheses are that the modern shape of the basin is due to: 1) flexure of the lithosphere under the surface load of the current topography, or 2) flexure under a subsurface load beneath the Rocky Mountains, or 3) a combination of both surface and subsurface loads. To test these hypotheses, spectral analysis and forward gravity modeling was conducted along three profiles located in the northern, central, and southern parts of the basin. Bouguer gravity power spectra along the profiles reveal 5 major density interfaces interpreted to represent the base of the lithosphere (at depths of 132 to 153 km), base of the crust (45-55 km), a mid-crustal boundary (about 20 km), the top of Precambrian basement (1-2 km), and a boundary between the Pierre Shale and Niobrara Formations within the pre-Laramide sedimentary section (-1-0 km). Flexural modeling shows that the shape of the basin can be fit with an elastic plate model having a line load of magnitude 2-5 x 1012 N/m and an elastic thickness of the lithosphere of 58-80 km. The location of the load is 90-115 km west of the Bouguer gravity minimum on each profile. The gravity anomaly associated with flexural subsidence of the basin, assuming the layered density structure derived from the spectral analysis, is calculated to reach a minimum of -60 mGal, only 15 % of the observed Bouguer gravity anomaly. The magnitude of the load is less than the present topography weight of 3.63-4.65 x 1013 N/m, indicating that the weight of the Rocky Mountain Front Range is only partially compensated by flexural isostasy. Since seismic data indicate a lack of a pronounced crustal root, a buoyant subsurface load is required (hypothesis 3). Forward gravity models, supplemented with available well and seismic refraction data, are developed to test four end-member hypotheses as to the location of the buoyant subsurface load. We consider in turn that the load lies entirely within the: (1) asthenosphere, (2) shallow lithosphere mantle, (3) lower crust, or (4) upper crust. The models show that the subsurface load is unlikely to lie entirely within any of the depth intervals investigated. The study indicates that the buoyant subsurface load is partitioned in some combination between low-density crust and/or low-density lithospheric and/or asthenospheric mantle. In all of the gravity models, the crust thickens abruptly at the boundary between the Rocky Mountains and Great Plains, from about 48 km beneath the Denver Basin to about 53 km beneath the Front Range Uplift.